Neuroendocrine Mechanisms of Acupuncture in the Treatment of Hypertension - Zhou, Wei (Hindawi Publishing Corporation, 2012)
Hypertension affects approximately 1 billion individuals worldwide. Pharmacological therapy has not been perfected and often is associated with adverse side effects. Acupuncture is used as an adjunctive treatment for a number of cardiovascular diseases like hypertension. It has long been established that the two major contributors to systemic hypertension are the intrarenal renin-angiotensin system and chronic activation of the sympathetic nervous system. Recent evidence indicates that in some models of cardiovascular disease, blockade of AT1 receptors in the rostral ventrolateral medulla (rVLM) reduces sympathetic nerve activity and blood pressure, suggesting that overactivity of the angiotensin system in this nucleus may play a role in the maintenance of hypertension. Our experimental studies have shown that electroacupuncture stimulation activates neurons in the arcuate nucleus, ventrolateral gray, and nucleus raphe to inhibit the neural activity in the rVLM in a model of visceral reflex stimulation-induced hypertension. This paper will discuss current knowledge of the effects of acupuncture on central nervous system and how they contribute to regulation of acupuncture on the endocrine system to provide a perspective on the future of treatment of hypertension with this ancient technique.